Uncovering business portfolio transformation processes: Development of a metric to measure and quantify business portfolio transformations - Sebastian Schönhaar (Technische Universität Bergakademie Freiberg, Fakultät für Wirtschaftswissenschaften, 2013)
Research on business portfolio restructuring has largely focused on antecedents and outcomes of single events such as acquisitions and divestitures, and on performance implications of diversification or refocusing strategies. Yet, longitudinal studies that investigate the transformation process of a business portfolio over time and its underlying strategic decision processes are rare due to a lack of an adequate metric that allows to measure and quantify major changes in a firm's business portfolio. The objective of this paper is to fill this gap through developing and proposing a systematic measurement system that allows to (a) identify firms that conduct a transformation of their business portfolio, (b) continuously measure the process and quantify the magnitude of a portfolio transformation, (c) measure both yearly and perennial changes in a business portfolio composition, and (d) determine a firm-individual transformation period with a clear transformation start date and end date. Furthermore, its practical applicability is illustrated based on a sample of the 100 largest European firms and with an in-depth analysis of Vivendi's business portfolio transformation from a construction to a media conglomerate. Concluding, further application areas of the metric as well as several directions for future research in this field are proposed. – – Die Forschung über Geschäftsportfoliorestrukturierung hat sich hauptsächlich auf Auslöser und Ergebnissen von einzelnen Transaktionen wie zum Beispiel Acquisitionen und Veräußerungen und auf Performance- Auswirkungen von Diversifikations- oder Refokussierungsstrategien fokussiert. Longitudinale Studien, die einen Transformationsprozess eines Geschäftsportfolios und die damit verbundenen Entscheidungsprozesse über einen Zeitraum untersuchen sind selten, hauptsächlich weil keine adäquate Metrik existiert, die es erlaubt Veränderungen eines Geschäftsportfolios zu messen und zu quantifizieren. Das Ziel dieser Studie ist es diese Lücke durch die Entwicklung einer solchen Metrik zu schließen. Diese erlaubt (a) Unternehmen, die eine Portfoliotransformation durchführen zu identifizieren, (b) kontinuierlich diesen Prozess und die Stärke der Portfoliotransformation zu messen, (c) sowohl jährliche als auch mehrjährige Veränderungen in einem Geschäftsportfolio zu mesen, und (d) eine unternehmensindividuelle Transformationsperiode mit einem eindeutig definierten Transformationsstart- und -endzeitpunkt zu bestimmen. Darüber hinaus wird die praktische Anwendung der Metrik anhand einer Auswahl der 100 größten europäischen Unternehmen und einer detaillierten Analyse von Vivendi's Geschäftsportfoliotransformation von einem Bauunternehmen hin zu einem Medienunternehmen illustriert. Abschließend werden weitere Anwendungsgebiete der Metrik sowie vielfältige zukünftige Forschungsgebiete aufgezeigt.
Keywords: L10; L25; 330; Business portfolio restructuring; Portfolio transformation; Strategy process; Transformation process; Transformation metric; Methodological study